Chromosome aberrations in cultured human lymphocytes exposed to trivalent and pentavalent arsenic. - Nordenson, Ingrid; Sweins, Agneta; Beckman, Lars (Scandinavian Journal of Work, Environment & Health, 1981)
Cultured human lymphocytes were exposed to trivalent (NaASO2) and pentavalent (Na2HAsO4) arsenic in concentrations comparable to the arsenic levels found in the urine of copper smelter workers. Significantly increased frequencies of chromosome aberrations (gaps, chromatid breaks, chromatid exchanges and chromosome breaks) were found after exposure to trivalent but not pentavalent arsenic. This effect was not found when nonstimulated (GO) lymphocytes were exposed to trivalent arsenic and then cultured. The rate of sister chromatid exchanges was also found to be increased after exposure to trivalent arsenic. Thus results suggest that trivalent arsenic is more genotoxic than pentavalent arsenic and that arsenic exerts its effect mainly during cell division.
Keywords: chromosome aberration; cultured human lymphocyte; exposure; pentavalent arsenic; sister chromatid exchange; smelter worker; trivalent arsenic; urinary arsenic